PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA GURU SDN 077 SEKIP - Leli Mahlinda (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2018)
This study aims to describe organizational culture, organizational commitment, work motivation and teacher performance in SDN 007 Sekip, to know and test the significant influence of organizational culture, organizational commitment and work motivation partially on teacher performance at SDN 007 Sekip and to know and test the influence significant organizational culture and organizational commitment and work motivation simultaneously teacher performance in SDN 007 Sekip. The method of this research is explanatory research with research population counted to 30 people. Sampling technique in this study using a sampling census that all members of the population into a sample of research. The sample in this research is the teachers at SDN 007 Sekip whics amounts 29 people, hereinafter referred to as the respondent. The result of data analysis shows that the variable condition of Organizational Culture, commitment, work motivation and teacher performance at SDN 007 Sekip are all in good enough category. Both simultaneously and partially the organizational culture, commitment and work motivation have a significant effect toward teacher performance SDN 007 Sekip. Job motivation partially have a significant influence toward teacher performance